Dye-sensitized solar cells with electrodeposited ZnO and Co(bpy)3 redox electrolyte: Investigation of mass transport in the electrolyte and interfacial charge recombination. (20th December 2017) - Ruess, Raffael; Haas, Sebastian; Ringleb, Andreas; Schlettwein, Derck
Abstract: Low-temperature electrodeposited ZnO has been used as a mesoporous photoanode in dye-sensitized solar cells and was investigated by photoelectrochemical techniques when used in combination with the organic sensitizer DN216 and the outer-sphere Co 2+/3+ (bpy)3 redox couple. The effect of the steric properties of the Co 3+ species on its diffusion inside the narrow channels in the porous matrix have been studied by electrochemical impedance spectroscopy and asymmetric mass transport characteristics in the cells were revealed which asked for an extension of existing models. It was found that a downward-shifted conduction band edge of the ZnO as well as a low electron lifetime limit the open-circuit photovoltage and thus the efficiency of the solar cells. The electron lifetime could be recovered by the addition of TBP to the electrolyte which is hindering electron recombination from the ZnO with the oxidized redox species. In this study it was demonstrated that it is possible to achieve high photocurrent densities with the Co(bpy)3 redox couple despite of the attenuated mass transport inside the porous network and steps for further optimization are discussed. Graphical abstract: Highlights: Application of reversible Co redox shuttle in ZnO-based dye-sensitized solar cells. Detection of asymmetric mass transport by electrochemical impedance spectroscopy. Extension of established equivalent circuit by an appropriate Warburg term. Control of interfacial recombination by chemical surface modification.